Analisis mutu dokumen perencanaan stratejik Rumah Sakit Umum Daerah: hasil, pelatihan manajemen stratejik di Indonesia = Quality of strategic planning documents: result of strategic planning training for district ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: This qualitative study analyted strategic planning documents as a result of a strategic planning training liar district hospitals in Indonesia, sponsored by the Department ()I' Internal Affairs. The theoretical hackground was that hospital directors who had been trained would manage the hospitals based on strategic planning principles. To perform this. hospitals nee,:l to formulate their strategic planning document based on external and internal envimninents. Methods: This study scrutinised 134 strategic planning documents of 230 district hospitals whose directors had been trained. A good strategic planning should fulfill twelve criteria, as follows: vision and mission. external and internal analysis, strengths, weaknesses. opportunities. threats, issues of development. main strategies, general strategies. functional strategies and program planning. Results: Result showed that 21{ out of 134 reviewed documents, were complete with an average value of 6.84 (score varies from (1-10). There was no difference between the average value of hospitals in Java (mean 5.92) and outside Java (mean 5.65). Among 12 criteria, the highest score (9.0(1) was on formulation of weakness. issues of development, and program planning. This was in accordance to the result of Kickpatrick's level 2 evaluation, indicating that the most comprehensible training materials in all training was strategic management, vision and mission, and application of customer-value principle. Analysis of Gross Regional Domestic Income (GRDl1 showed that areas with high GRIM had lower score on strategic planning. Further analysis with single regression revealed that average score of district hospitals- strategic planning and PDRB had a negative relationship albeit non-significant. Conclusion: PDRB is not a good predictor for district hospital's strategic planning. The study recommends further analysis on predictors of hospital strategic planning and process analysis of hospital strategic planning formulation. "The outcome of strategic management training on hospital performance should also he evaluated 3-5 years after the training.